Design and Development of Augmented Reality-Based Learning Media Using Unity 3D for the TJKT Elective Subject among Grade XI Students at SMKN 8 Padang - Agil Surya Norama; Indra Wijaya; Doni Pernanda (Darul Yasin Al Sys, 2026)
Limited access to computer-networking equipment, combined with continued reliance on verbal explanations and static images, presents a persistent challenge in teaching the Computer and Telecommunications Network Engineering (TJKT) elective subject. This study aimed to develop and evaluate augmented reality (AR)-based learning media using Unity 3D for Grade XI students at SMKN 8 Padang. A research and development approach was employed using the ADDIE model, comprising analysis, design, development, implementation, and evaluation. The participants included three expert validators and 31 Grade XI TJKT students selected through purposive sampling. Data were collected using validation sheets, practicality questionnaires, observations, and learning-achievement tests and analyzed through quantitative and qualitative descriptive techniques. The developed learning media achieved a validity score of 93.00%, a practicality score of 94.08%, and an effectiveness score of 89.52%, placing it in the very valid, very practical, and very effective categories, respectively. The application provides interactive three-dimensional visualizations of computer-networking devices, thereby supporting more concrete learning experiences despite limited access to physical equipment. These findings demonstrate the feasibility of integrating AR-based media into vocational computer-networking education and strengthen the evidence supporting AR-assisted vocational learning. Further development should incorporate markerless AR, improve cross-platform compatibility, involve larger samples, and employ more rigorous experimental designs to establish comparative learning effects.